The Role of Network for Alternative School: The Ways Indonesians CSOs Manage Networking to Support Their Agenda on Education - Umar Baihaqki;; Abdi Rahmat (Laboratorium Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Jakarta, 2017)
This article discussed the role of civil society organization networks to their educational agenda. Several member of civil society formed voluntary based organization to organized informal schooling institute on that is commonly known as sekolah alternatif or alternative school. This school is a community based institution that aims at delivering education service for underprivileged children. Four CSOs were chosen as case studies to learn how they maintained their networks to mobilize resources for the alternative school. The networks were classified into two, namely internal networks based on voluntarism value, and external networks that maintained to provide additional resources as means to improve the learning services. The network dynamics indicated that both the individual social capital and the institutional social capital contributeed to the breadth of network.